Development of an online seismic disaster monitoring system in Yalong river - Liu, Jian; Zhang, Peng; Zhang, Chen; Meng, Qing-xiang; He, Zijie; Feng, Tao (Frontiers in Earth Science, 2026)
Rapid post-earthquake assessment of large dams is essential in seismically active mountain regions. We develop an online dam-safety monitoring framework for cascade hydropower stations in the Yalong River Basin. Two earthquake risk indices (R1 and R2), derived from a reservoir seismic network and a dam strong-motion system, trigger intensified monitoring with prioritized data acquisition and an automated preliminary report within about 15 min after shaking; a concise post-earthquake brief is produced within about 30 min when the workflow is completed. An elastoplastic deformation monitoring model is coupled with static and dynamic structural analyses to evaluate displacement/stress states and infer potential damage. A three-dimensional early-warning matrix integrates monitoring, inspection, and structural-calculation results to provide graded safety assessment. Basin-scale application demonstrates efficient decision support and helps quantify dam–valley rock-mass responses in a complex seismotectonic setting.